The Caitlin Clark Effect: Evidence of Athlete-Driven Market Disruption in Women’s Collegiate Basketball - Lawrence W Judge; Jeffrey C. Petersen (Journal of Applied Sports Management, 2025)
Caitlin Clark’s emergence as a generational collegiate basketball talent triggered a profound shift in consumer behavior, known as the “Caitlin Clark Effect” (CCE) (Lucas, 2025). This study examined attendance and venue utilization data from the University of Iowa’s women’s basketball program, spanning pre-, during-, and post-Clark periods. Results from one-way ANOVA analyses showed a statistically significant increase in average game attendance (home, away, and neutral), rising from 5,387 pre-Clark to 13,877 in her senior year (p < .001), with a sustained post-Clark average of 9,890. Arena capacity utilization followed a similar trajectory, increasing from 37.3% to 92.4%. Notably, post-Clark utilization remained at 74.3%, indicating durable fan interest. These findings provide time-sequenced evidence of a singular athlete catalyzing lasting institutional and market change in women’s collegiate sports. The study advances sport business theory by illuminating the strategic implications of athlete-driven branding and challenges assumptions underpinning facility planning and resource allocation.
Keywords: attendance; basketball; capicity